Gut wall integrity in exclusively breastfed vs. formula-fed infants - Nur Hayati; Muzal Kadim; Irawan Mangunatmadja; Soepardi Soedibyo; Evita Bermansyah Ifran; Hikari Ambara Sjakti (Paediatrica Indonesiana, 2016)
Background Breast milk has bioactive substances that modulate gastrointestinal maturation and maintain mucosal integrity of the gut in infants. Markers that are both non-invasive and reliable, such as fecal alpha-1 antitrypsin (AAT), calprotectin, and secretory immunoglobulin A (sIgA) have been used to assess gut integrity in adults. Higher AAT levels may imply greater enteric protein loss due to increase intestinal permeability of immaturity gut.Objective To assess and compare gut integrity of exclusively breastfed (BF) and exclusively formula fed (FF) infants aged 4-6 months.Methods Subjects were 80 healthy infants (BF=40; FF=40), aged 4-6 months who visited the Pediatric Polyclinic at St. Carolus Hospital, and lived in Pasar Minggu or Cempaka Putih Districts, Jakarta. The fecal AAT was analyzed by an ELISA method. Mann-Whitney and unpaired T-test were used to analyze possible correlations between feeding type and gut integrity.Results The BF group had significantly higher mean fecal AAT than the FF group (P=0.02). Median sIgA levels were not significantly different between groups (P=0.104). The FF group had a higher mean fecal calprotectin level but this difference was also not significant (P=0.443). There was a significant correlation between breastfeeding and mean fecal AAT level (P=0.02), but no significant correlation with calprotectin (P=0.65) or sIgA (P=0.26).Conclusion The breastfed group shows better mucosal integrity compared to the formula fed group. Higher mean fecal AAT level in the BF group is related to the AAT content of breast milk. Therefore AAT content of BF group is actually lower than formula fed group which shows greater mucosal integrity in BF group.